2016
DOI: 10.1177/1091142116651488
|View full text |Cite
|
Sign up to set email alerts
|

What Explains the Redistribution Achieved by the Italian Personal Income Tax? Evidence from Administrative Data

Abstract: We analyze the Italian personal income tax (PIT) in the light of the different tools available to the government to achieve income redistribution. We focus in particular on three mechanisms: marginal tax rates, deductions, and tax credits. Exploiting an extended version of the standard Pfähler decomposition, we estimate the contribution of each of these three tools to the overall redistributive effect of the PIT using administrative data on more than 1.3 million individual tax returns. Our estimates suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…analyse the distributional impact and the collateral consequences of tax expenditures showing that "the interactions of tax expenditures will be one of the most difficult aspects of any reform effort". Burman and Phaup (2012) points out how classifying tax expenditures as tax cuts rather than spending has led over time to higher taxes, bigger government, and an inefficient spending mix due to too much tax spending; Barbetta et al (2018) analyzing the Italian personal income tax shows that it is only a few major tax expenditures (the tax credit for employment and retirement income) that determine the total redistributive effect, while on the contrary most minor expenditures have no significant impact on redistribution.…”
Section: Literaturementioning
confidence: 99%
“…analyse the distributional impact and the collateral consequences of tax expenditures showing that "the interactions of tax expenditures will be one of the most difficult aspects of any reform effort". Burman and Phaup (2012) points out how classifying tax expenditures as tax cuts rather than spending has led over time to higher taxes, bigger government, and an inefficient spending mix due to too much tax spending; Barbetta et al (2018) analyzing the Italian personal income tax shows that it is only a few major tax expenditures (the tax credit for employment and retirement income) that determine the total redistributive effect, while on the contrary most minor expenditures have no significant impact on redistribution.…”
Section: Literaturementioning
confidence: 99%
“…Additional reductions are available for parents of young children, working mothers, discharged soldiers and many other categories. The credits along with marginal tax rates contribute to a more equitable distribution of income (Barbetta et al, 2018).…”
Section: Other Changesmentioning
confidence: 99%
“…They found that, while the distributional effects of deductions vary substantially, the overall net effect of tax expenditure for individual income tax is regressive. Barbetta et al ( 2018 ) used administrative data to analyze the redistributive effects of Italy’s PIT and showed that itemized deductions tend to have little notable impact on income redistribution. Despite its importance, our understanding of the topic remains limited, and the few studies in the literature do not offer a consensus on income taxation’s redistributive impact.…”
Section: Literature On Personal Income Tax Deductionsmentioning
confidence: 99%
“…While itemized deductions are traditionally thought to favor wealthier families in anecdotal narratives, mixed findings occur on this line of inquiry when different PIT systems are presented in different policy settings. Barbetta et al ( 2018 ) believe that most of the itemized expenditures in Italian PIT do not show any sizable impact on redistribution. Cauble ( 2017 ) argues that Trump’s U.S. tax reform may see itemized deductions disproportionately benefitting higher-income individuals even with the increase in the standard deduction and the elimination or reduction in various itemized deductions.…”
Section: Personal Income Tax In Taiwanmentioning
confidence: 99%